Jawaharlal Nehru’S Contribution to Indian English Prose: Unveiling the Legacy: Analyzing Jawaharlal Nehru's Contribution to Indian English Prose (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Jawaharlal Nehru enjoys an enviable position in IndianEnglish prose in the foreword to A Studyof Nehru, Dr. Rajendra Prasad writes: